Opto-Electronic properties of BN-ring insertions in Circumacenes: the case of Coronene and Ovalene. (May 2020) - Mocci, P; Cardia, R; Bosin, A; Cappellini, G
Abstract: We report a comparative computational analysis on the electronic and optical properties of some emblematic carbonaceous planar molecules after BN substitutions. In particular, we focused on Coronene (C24 H12 ) and Ovalene (C32 H14 ) molecules (belonging to the Circumacenes family) after different hexagonal-Boron-Nitride-ring insertions. We have performed all-electrons Density Functional Theory and Time Dependent DFT calculations using a localized Gaussian basis-set combined with the hybrid exchange-correlation functional B3LYP. For all the systems, we calculate the main molecular electronic and optical properties and we discuss if the mixed C-BN-ring-substituted clusters could be a potential attractive alternative or integration with respect to their C-made compounds, for both fundamental and application research.